Orhan Pamuk's novel "The Red-Haired Woman" within the framework of intertextuality theory - Susareishvili Maka (Foundations and Trends in Modern Learning, 2024)
: Intertextuality has become integral to postmodern literature. The term "intertextuality" was first introduced by Julia Kristeva, a poststructuralist theorist, in the latter half of the 20th century during the formation of poststructuralism. Post-structuralism posits that a text does not exist in isolation; rather, each text is intricately connected to others, forming a "global text."Since the 1960s, Julia Kristeva has continued to develop this theoretical framework. Roland Barthes expanded upon her research, while Michael Rifater proposed an alternative theory that integrates the reader into the concept, framing intertextuality as a product of reader perception.When analyzing intertextual relations within the novel "The Red-Haired Woman," one can discern traces of other texts interwoven into its fabric. The novel is distinguished by its diverse intertextual connections, which are not merely peripheral but fundamental to its narrative and thematic structure. "The Red-Haired Woman" blends classical myths, historical narratives, and religious texts.The narrative draws heavily from Sophocles' Greek tragedy "Oedipus the King" and Ferdowsi's monumental Eastern epic "Shahnameh." Orhan Pamuk reinterprets these narratives through a contemporary existential lens.The Oedipus myth centers on patricide and self-discovery, where Oedipus's unwitting killing of his father determines his tragic fate and identity. Similarly, patricide is a central theme in Ferdowsi's "Shahnameh," where Rostam's accidental slaying of his son, Sohrab, underscores the inexorable force of destiny."The Red-Haired Woman" engages in a dialogue with these texts, aiming to reconcile two distinct cultural and intellectual realms. The author employs this dialogue to explore a convergence of ideas, symbolizing the dichotomy between East and West in intellectual and cultural contexts.